1990
DOI: 10.1007/bf03183912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage on germination ofDioscorea composita (Dioscoreaceae) seeds

Abstract: Effects ofstorage were tested on germination of Dioscorea composita (Dioscoreaceae) seeds. Freshly collected seeds and seeds stored at 25"C in paper bagsfrom 1 to 11 mo or for 4 and 5 yr were used in most of the experiments. Seeds were testedfor germination at 20,25,30, 35, 25-20, 25-30, and 25-35"C in white light and in darkness. Initiation ofgermination was delayed in freshly harvested seeds, and dormancy was reduced in seeds stored for about 9 mo. Viability of the seeds decreased after 4 and 5 yr ofstorage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Dioscorea trifida seed dormancy was broken faster than in other species of Dioscorea, such as D. rotundata, which has a dormancy period of three to four months after harvest and a relatively low germination rate due to embryo or endosperm development issues (Sadik 1976). An even longer dormancy time was observed for D. composita Hemsl., which broke dormancy only after storage for nine months (Viana and Felippe 1990). These results suggest that D. trifida presents a physiological dormancy, as do other Dioscorea species, such as the medicinal D. villosa L. (Langhu and Deb 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Dioscorea trifida seed dormancy was broken faster than in other species of Dioscorea, such as D. rotundata, which has a dormancy period of three to four months after harvest and a relatively low germination rate due to embryo or endosperm development issues (Sadik 1976). An even longer dormancy time was observed for D. composita Hemsl., which broke dormancy only after storage for nine months (Viana and Felippe 1990). These results suggest that D. trifida presents a physiological dormancy, as do other Dioscorea species, such as the medicinal D. villosa L. (Langhu and Deb 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Germination of T. communis was satisfactory, and prone to improvement with simple osmotic treatments. Long germination time was found in other Dioscoreaceae species (Sadik, 1977;Viana and Felippe, 1990), where it was shown that post-maturation after harvest can shorten dormancy. Therefore, this option could be assayed for T. communis too, to reduce the risks connected with a too long germination time.…”
Section: Discussionmentioning
confidence: 79%